Bis (benzothiazolyl) benzene and Bis (benzothiazolyl)-4-methyl benzene) Transition Metal Complexes as Catalysts for Ethylene Polymerization: Synthesis, Characterization and Polymerization Activity - Elagab, Hamdi Ali (Orbital: The Electronic Journal of Chemistry, 2017)
A series of 16 complexes of 1,2-bis(benzothiazolyl) benzene and 1,2-bis(benzothiazolyl)-4-methyl benzene compounds with Ti(IV), Zr(IV), V(III), Fe(III), Fe(II), Co(II), Ni(II) and Cu(II) were synthesized and characterized. After activation with methylalumoxane (MAO), these complexes showed variable activities towards ethylene polymerization. The polymerization activities of the catalyst system 3, 5, 7 and 15 /MAO were investigated under different polymerization conditions. The highest activity 625 [Kg PE / mol Cat. H] is obtained by the catalyst system 5/MAO at 50 °C and cocatalyst concentration of 1000 equivalents. The produced resins showed high molecular weights associated with broad or even bimodal molecular weight distributions for all catalysts systems except the polymers produced with nickel catalysts 9 and 17/MAO. DOI: http://dx.doi.org/10.17807/orbital.v9i1.945